Parental Occupational Exposure is Associated With Their Children's Psychopathology: A Study of Families of Israeli First Responders. Issue 11 (November 2020) - Kishon, Ronit; Geronazzo-Alman, Lupo; Teichman, Meir; Teichman, Yona; Cheslack-Postava, Keely; Fan, Bin; Duarte, Cristiane S.; Wicks, Judith; Musa, George J.; Djalovski, Amir; Tadmor, Boaz; Moreno, Diana Rodriguez; et al.
Abstract : Objective: To examine the association between parental occupational exposure to traumatic events and their children's mental health in families of First Responders (FRs), a neglected area of research. Methods: In 208 families of Israeli FRs, children's symptoms and comorbidity patterns of seven psychiatric disorders were regressed on parental work-related variables, controlling for relevant covariates. Results: Having a father working as a FR and higher paternal exposure were associated with a greater number of separation anxiety and posttraumatic stress symptoms, respectively. Maternal exposure was associated with a greater number of symptoms of generalized anxiety, panic disorder, depression, and oppositional defiant disorder, and with increased odds of comorbid internalizing symptomatology. Conclusions: Additional research on children of FRs is encouraged. An adaption to this understudied population of family-centered interventions available for military families could inform targeted prevention efforts. Abstract : Supplemental Digital Content is available in the text